History, Archaeology and Ideology : Essays on Intellectual and Social History of Early India - Shrimali, Krishna Mohan, (Brill | Manohar Publishers & Distributors, 2024)
In a country as vast and varied as India and that too with an extraordinary long and continuous history spanning over several millennia, historical processes of its development just cannot be unilinear. Since such diversi-fied processes are being presented in this monograph in a broad material background, it becomes imperative that the simultaneous presence of varied production processes in different parts of the subcontinent is recognised and underlined. In fact, modes of production and productive forces as factors behind historical transformations through the centuries have been stressed in most of the contributions here. Be it the issue of social formations and their dynamism, or of the analysis of the so-called 'feminist' writings; comprehending the ground realities of the lowest orders of the social fabric, or of providing fresh insights for delineating the developmental stages of Indian arts; construction of the apparatus of knowledge systems in early India, or of establishing the true identity of common Indian human being; the central focus has always been on the ordinary toiling people of the country. Even archaeologists have been exhorted to make them the real subjects of enquiry and data retrieval in their diggings and excavation reports. Long tradition of questioning going back to the Ṛgveda, social bases of knowledge systems, construction of 'heritage' and its sustenance in the face of challenges of 'development', ideological confrontations with neo-colonialist strains and incessant concern about communalisation of writings on Indian history and archaeology are other themes that have been highlighted here. Sixteen essays of this anthology cover almost the whole gamut of five millennia of Indian history.